IN VIVO AMELIORATIVE POTENTIAL OF CAFFEIC ACID AGAINST HEPATOTOXICITY AND NEPHROTOXICITY INDUCED BY MERCURIC CHLORIDE IN ALBINO WISTAR RATS - MANJU, MANOGARAN; GANESAN JAGADEESAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current experimental study is designed to scrutinize the possible defensive effect of caffeic acid (CA) against mercury-induced hepatotoxicity in male rats. Methods: During the treatment periods, a sub-lethal dose of HgCl2 (1.29 mg/kg body weight) was given to rats for 15 days through oral administration and the CA was administrated for 15 days, on mercuric intoxicated rats were observed. After completing the programmed period of experimental work, the blood was drawn through a micro glass tube in the ocular region and separated the serum by centrifuge. Results: The subsequent serum enzymes were analyzed as the alkaline phosphatase (ALP), alanine transferase (ALT), aspartate transaminase (AST), and lactate dehydrogenase (LDH). Further, the bilirubin, albumin, total cholesterol, urea, and creatinine levels were also noticed in the blood serum of both normal and treated rats. CA is one of the well-known phenolic compounds, and a strong antioxidant helps to prevent oxidative damage and reducing oxidative stress. The biological action of liver biomarker enzymes such as ALT, AST, ALP, and LDH was significantly enhanced and at the same time the drastic increased in the level of albumin was all together decreased. The level of bilirubin, total cholesterol, urea, and creatinine was significantly increased in HgCl2 intoxicated rats. When the treatment of CA on mercury intoxicated rats for 15 days (5 mg/kg body weight), in the serum enzymes (ALT, AST, ALP, and LDH) also declined to near normal level. The level of bilirubin, total cholesterol, urea, and creatinine activities was also significantly declined to near normal level when compared to mercury-treated group. The level of albumin was significantly enhanced. The CA alone treatment showed the enhanced antioxidant levels and not any alteration in the levels of biochemical parameters when compared to control. Conclusion: These observations of the present experimental work demonstrated the detoxify effects and defensive effect of CA against HgCl2 toxicity in liver tissue.